Manajemen Keuangan dan Kinerja Organisasi dalam Meningkatkan Mutu Lulusan - Sri Winarsih (Institut Agama Islam Negeri Purwokerto, 2020)
Management is the whole process of carrying out a job through other people carried out by two or more people to achieve a common goal that has been determined or decided previously, it can also be said that management is an organizational tool. Meanwhile, financial management is one of the management substances in educational institutions that will determine the course of educational activities at the institution. Financial management activities are carried out through the process of planning, organizing, directing, coordinating, supervising or controlling. The function of financial management is to obtain, and seek opportunities for funding sources for activities at the educational institution, in order to be able to use funds effectively and not violate the rules, and to make transparent and accountable financial reports. The principles of financial management are transparency, accountability, effectiveness, and efficiency. Meanwhile, organizational performance is the results obtained by an organization, both profit-oriented and non-profit-oriented organizations that are produced over a period of time and are measurable work achievements, related to the ability and strength of the organization as a whole to achieve organizational goals. Performance appraisal is basically used to assess the success or failure of implementing activities, programs and/or policies in accordance with the goals and objectives that have been set in order to realize the vision and mission of government agencies. The management model and strategy for improving the quality of graduates in educational institutions can be pursued through, among others: (a) Total Quality Management Theory. (b) Organizing Business For Excelency Theory. Educators must also master and be able to implement four competencies, to realize their professional performance, namely pedagogic competence, personality competence, professional competence and social competence. In addition, excellent service and management must be optimized to improve the quality of graduates in these educational institutions, so that the